Potret Unit Usaha Pondok Pesantren Yayasan Waqaf Ar Risalah Sumatera Barat - Mayang Bundo; Doni Eka Putra; Afriyanti Afriyanti (Jurnal Ilmiah Ekonomi Islam, 2023)
This study uses a qualitative approach using descriptive methods. The research location is in the area of the Waqaf Ar Risalah Islamic Boarding School which is located at Jl. Cold Water RT 01 RW IX, Balai Gadang Village, Tangah City District, Padang City, West Sumatra. Data analysis techniques in this study used qualitative data analysis. Islamic boarding schools as educational institutions have a strategic role in instilling Islamic values. Besides that, as an educational institution, pesantren is responsible for the goals of national education, one of which is self-sufficiency. With their independence, Islamic boarding schools are currently required to carry out business activities to support the survival of Islamic boarding schools so that they can become self-financing or self-supporting. The development of business units in Islamic Boarding Schools is inseparable from the results of good management and management of administrators and employees. In its operation in the existing business units, there has been no involvement from the students such as in the sharia microfinance business units, convection, book and uniform business units. However, this does not reduce the existence of business units to develop further. On the other hand, student involvement has a positive value for fostering a spirit of entrepreneurship and independence.